Inhibitory effect of bufalin and cinobufagin on steroidogenesis via the activation of ERK in human adrenocortical cells - Kau, Mei-Mei (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Bufalin and cinobufagin exhibit cardiotonic and natriuretic activities. The aim of this study was to evaluate the effects of bufalin and cinobufagin on aldosterone and cortisol secretion and their mechanisms of action in human adrenocortical cells (NCI-H295). EXPERIMENTAL APPROACH: H295 cells were incubated with bufalin or cinobufagin in the presence or absence of angiotensin II (Ang II), forskolin, 8-Br-cAMP, corticosterone or deoxycortisol. The role of ERK1/2 was studied by use of the inhibitor of MEK (U0126). The binding of transcription factor steroidogenic factor 1 (SF-1) to steroidogenic acute regulatory (StAR) gene promoter was analysed by EMSA. KEY RESULTS: Bufalin and cinobufagin markedly inhibited basal, Ang II-, forskolin- or 8-Br-cAMP-stimulated aldosterone and cortisol secretion, and the conversions of corticosterone to aldosterone and deoxycortisol to cortisol. Bufalin and cinobufagin also inhibited StAR protein expression and SF-1 binding to StAR gene promoter. They both increased phosphorylation of ERK1/2, and U0126 fully abolished these effects on ERK1/2 in H295 cells. Furthermore, U0126 reversed the inhibitory effects of bufalin and cinobufagin on StAR protein expression and the binding of SF-1 to StAR gene promoter. However, U0126 did not completely reverse their inhibitory effects on aldosterone and cortisol release. CONCLUSIONS AND IMPLICATIONS: The inhibitory effects of bufalin and cinobufagin on steroidogenesis of aldosterone and cortisol were associated with inhibition of aldosterone synthase and 11β-hydroxylase, as well as the suppression of StAR protein expression and SF-1 binding to StAR promoter via the phosphorylation of ERK1/2 in H295 cells.